2006
DOI: 10.1136/vr.159.20.662
|View full text |Cite
|
Sign up to set email alerts
|

Current attitudes of cattle practitioners to pain and the use of analgesics in cattle

Abstract: A questionnaire to examine the attitudes and perceptions of cattle practitioners to pain in cattle was sent to 2398 practitioners working in the UK, and 641 responses were received. From the range of procedures and conditions outlined in the questionnaire, claw amputation was scored as the most painful procedure undergone by adult cattle (assuming no analgesic drugs were administered), and neck calluses were scored as the least painful condition experienced by adult cattle. The pain associated with dystocia wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
256
12
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(320 citation statements)
references
References 16 publications
29
256
12
10
Order By: Relevance
“…In addition, the small sample size of operations that fell into this category means this finding should be interpreted with caution. Although studies have shown that dystocia is one of the most painful conditions in adult cattle (Huxley and Whay, 2006;Laven et al, 2009), few survey respondents reported administering pain medication to the cow at calving. Even fewer reported giving non-steroidal anti-inflammatory drugs (NSAIDs) to the calf.…”
Section: Calving Seasonmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the small sample size of operations that fell into this category means this finding should be interpreted with caution. Although studies have shown that dystocia is one of the most painful conditions in adult cattle (Huxley and Whay, 2006;Laven et al, 2009), few survey respondents reported administering pain medication to the cow at calving. Even fewer reported giving non-steroidal anti-inflammatory drugs (NSAIDs) to the calf.…”
Section: Calving Seasonmentioning
confidence: 99%
“…Even fewer reported giving non-steroidal anti-inflammatory drugs (NSAIDs) to the calf. This may be because the effects of dystocia on the cow are perceived as being more painful than in the calf (Huxley and Whay, 2006;Laven et al, 2009). Despite this perception, it is common for calves to endure severe injury, inflammation or bruising, which can impact calf vitality, health and performance (Murray and Leslie, 2013).…”
Section: Calving Seasonmentioning
confidence: 99%
“…This may be linked to the greater empathy for pain in animals and more positive attitudes towards animal welfare reported in women (Capner et al, 1999;Huxley and Whay, 2006;Väisänen et al, 2008;Kielland et al, 2009;Laven et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Women are provided with pain relief either through gas and air, or via an epidural during labor; however, this is not possible in animals as there is concern that the animal would no longer feel contractions and stop pushing. Difficulties during parturition are considered painful enough to administer analgesics post-partum, particularly in dairy cattle [60]. Cattle receiving post-partum analgesia tended to feed quicker [61,62] and resume activity sooner [63] compared with controls, highlighting the importance of considering the effect of parturition on animal welfare.…”
Section: Parturitionmentioning
confidence: 99%
“…Where there are licensed drugs available, their use in practice is still limited [60,134,135]; Becker et al [134] found almost 70% of veterinarians carried out painful foot treatment interventions without any form of pain relief. Commonly reported reasons for not administering analgesia to farm animals include the cost to the farmer, withdrawal periods for drug residues, few licensed analgesics or anesthetics approved for use in production animals, and particular difficulty in recognizing, assessing and evaluating pain [10,60,135].…”
Section: Pain Managementmentioning
confidence: 99%